PERAN PUSTAKAWAN DALAM MENINGKATKAN VISIBILITAS REPOSITORI INSTITUSI DENGAN MEDIA FACEBOOK - Andres Amrulloh (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
This study aims to explain and know the role of librarians in the digital age in increasing the visibility of institutional repositories on the library web by uploading local content book annotations on Facebook media. The study was conducted by recording the books uploaded on Facebook for a year. The data source for this study was the Facebook of Bogor Botanic Gardens Library in 2018. The analysis was done descriptively. The results of the study showed the number of people who saw the book annotation posts during the year were 2687 people out of the 26 titles uploaded, 114 people said they liked, and 97 people clicked on this post. Data from facebook is significant with 2018 online library web catalog visits, totaling 1826 people, from a total of 4661 web visits. The three most popular book titles are Conservation Biology, Rafflesia 19 likes, Amorphophallus Indonesia 15 likes, Graveyards in the Bogor Botanical Gardens, 13 likes.